PERAN MEDIA SOSIAL TERHADAP PEMASARAN IKAN NILA DI DESA JARAKORE KECAMATAN SAHU KABUPATEN HALMAHERA BARAT - Budiman, Josse; Musdhalifah Kholil; Zakeus Dadi (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
This research aims to: (1) Find out the role of the media in marketing tilapia in Distancere Village, Sahu District, West Halmahera Regency. This research was designed quantitatively, which took place in Distancere Village in May-August 2024. The sample was determined as 20 people. Primary data was obtained through interviews and observations using questionnaires, secondary data was obtained from BPS, journals, theses and other relevant.  Data analysis used to answer the research objectives is a Likert scale using a score of 1-5 (1: very no role, 2: no role, 3: role 4: quite role and 5: very role). The research results show that the role of WhatsApp social media in marketing tilapia in Distancere Village has an average value of 4.03 percent in the role category. The role of Facebook's social media has an average of 3.97 percent in the moderately important category and the role of Instagram's social media shows an average of 4.06 percent in the important category.